PENGARUH KOMPENSASI WORK ENGAGEMENT DAN WORK LIFE BALANCE TERHADAP KEPUASAN KERJA PENULIS FREELANCEDI REDAKSI AIRIZ - Endang Winarsih; Santosa Tri Prabawa; Noviana Diah Saputri (JURNAL WIRANOMIKA, 2023)
This research is a quantitative study that aims to determine the influence of compensation, work engagement and work-life balance on job satisfaction of the freelance writers in the Redaksi Airiz. The study used a sample size of 40 respondents, with non-probability purposive sampling. Data collection techniques using questionnaires. The data analysis techniques used multiple regression test with T test to prove the partial hypothesis and F test to prove simultaneous hypothesis. The tool used to analyze the data using statistical application software SPSS 25. Based on the results of testing the hypothesis T test, the compensation has a positive and significant influence on job satisfaction. Meanwhile, the work engagement has a positive and significant influence on job satisfaction. AndÂ  work life balance does not significantly influence job satisfaction. Meanwhile, the F test found there is an influence between the variables of compensation, work engagement and work-life balance on job satisfaction. The results of the determination test (R2) in this study indicates that there is an influence relationship strong positive relationship between compensation, work engagement and work life variables balance on job satisfaction.Keywords : compensation, work engagement, work life balance, job satisfication, freelance